2008
DOI: 10.1096/fj.07-105015
|View full text |Cite
|
Sign up to set email alerts
|

Analogous oligo‐acyl‐lysines with distinct antibacterial mechanisms

Abstract: Bactericidal properties were recently shown to emerge from hydrophobicity and charge buildup in oligo-acyl-lysine (OAK) peptide mimetics. Toward understanding the attributes that govern the activity of this novel antimicrobial system, we compared the functional and mechanistic properties of a known octamer and a newly generated hexamer analog. The data provide strong evidence for multiple similarities that included high tissue stability, low hemolysis, large-spectrum antibacterial activity in vitro, and the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
99
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(106 citation statements)
references
References 52 publications
7
99
0
Order By: Relevance
“…Some AMPs that inhibit DNA synthesis bind nonspecifically to DNA. For example, the amphibian AMP, the a-helical AMP buforin II, can penetrate the cell membrane without causing its disruption, and inhibits cellular functions by binding to nucleic acids (Park et al, 1998;Kobayashi et al, 2000;Rotem et al, 2008;Sarig et al, 2011;Gottschalk et al, 2013). Therefore, to investigate whether the inhibition of DNA synthesis could be due to the binding of FL9 to bacterial DNA, a gel retardation assay was performed.…”
Section: Fl9 Interferes With Dna Synthesis and Binds Dna In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Some AMPs that inhibit DNA synthesis bind nonspecifically to DNA. For example, the amphibian AMP, the a-helical AMP buforin II, can penetrate the cell membrane without causing its disruption, and inhibits cellular functions by binding to nucleic acids (Park et al, 1998;Kobayashi et al, 2000;Rotem et al, 2008;Sarig et al, 2011;Gottschalk et al, 2013). Therefore, to investigate whether the inhibition of DNA synthesis could be due to the binding of FL9 to bacterial DNA, a gel retardation assay was performed.…”
Section: Fl9 Interferes With Dna Synthesis and Binds Dna In Vitromentioning
confidence: 99%
“…In addition to membrane disruption, several studies have shown that some AMPs also have the ability to traverse the cytoplasmic membrane and target intracellular molecules such as DNA and RNA (Brogden, 2005;Jenssen et al, 2006;Peschel & Sahl, 2006;Makobongo et al, 2012 interaction of AMPs with DNA may damage DNA and induce the SOS response (Gunderson & Segall, 2006;Rotem et al, 2008;Sarig et al, 2011). The SOS regulon comprises genes essential for DNA repair and restart of stalled or collapsed replication forks.…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria were cultured in suitable broth medium (brain heart infusion or LB). The MIC was determined using a slightly modified NCLSI microdilution assay (44) to enable comparison with previously characterized OAKs (42)(43)(44)(45)(46). For pH and salt variations, the culture medium was brought to the desired pH by adding NaOH or HCl (1 N) or to the desired saline concentration by adding NaCl to the culture medium.…”
Section: Organization In Solutionmentioning
confidence: 99%
“…The DNA binding assay was performed using pUC19 plasmids that were extracted from E. coli K-12, as previously described (46). Briefly, the plasmids were preincubated with the OAKs at the specified concentrations (1 h; 37°C), followed by washes and incubation with the DNase BamHI (1 h; 37°C).…”
Section: Organization In Solutionmentioning
confidence: 99%
See 1 more Smart Citation